2007
DOI: 10.1007/s12098-007-0004-3
|View full text |Cite
|
Sign up to set email alerts
|

Immunization in urbanized villages of Delhi

Abstract: Immunization evaluation surveys have shown a wide variation across regions, states and different strata of the society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
54
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 6 publications
(15 reference statements)
15
54
5
Order By: Relevance
“…Chhabra P et al observed similarly that dropout rate increases with subsequent vaccination. 18 Over all dropout rate (Birth -Measles) in our study was 18.91 % which is less than study done in urbanized villages of Delhi where it was 49%. 18 In our study common reasons for partial/non immunization were postponed due to illness of child (29%), lack of knowledge of immunization schedule/ subsequent doses (28%) and lack of motivation (20%).…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Chhabra P et al observed similarly that dropout rate increases with subsequent vaccination. 18 Over all dropout rate (Birth -Measles) in our study was 18.91 % which is less than study done in urbanized villages of Delhi where it was 49%. 18 In our study common reasons for partial/non immunization were postponed due to illness of child (29%), lack of knowledge of immunization schedule/ subsequent doses (28%) and lack of motivation (20%).…”
Section: Discussioncontrasting
confidence: 62%
“…18 Over all dropout rate (Birth -Measles) in our study was 18.91 % which is less than study done in urbanized villages of Delhi where it was 49%. 18 In our study common reasons for partial/non immunization were postponed due to illness of child (29%), lack of knowledge of immunization schedule/ subsequent doses (28%) and lack of motivation (20%). Similar findings are noted by Kar M et al in their study, common reasons being un well child, lack of knowledge of immunization schedule and migration to native village.…”
Section: Discussioncontrasting
confidence: 62%
“…89% of the participants thought that there is a relation between the parent's educational level and taking the kids' vaccinations, Several studies have found that actually Completeness of vaccination was significantly correlated with knowledge of mothers on immunization (25,26).…”
Section: Discussion:-mentioning
confidence: 99%
“…The coverage levels were highest for BCG (82.7%) and DPT/OPV1 (81.5%) and lowest for HBV3 (24.3%). About 65.3% had received primary immunization while only 41.6% of children had received MMR vaccine [14]. …”
Section: Discussionmentioning
confidence: 99%